2022
DOI: 10.20944/preprints202207.0217.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Anti-DENV IgG Among Routine Bangladeshi Blood Donors, and Strategies for the Future

Abstract: Background: Dengue is the most common arthropod-borne sickness worldwide, impacting at least 50 million people each year. The dengue virus has four primary serotypes. Infection with one serotype confers homotypic immunity but not heterologous immunity, and secondary infections may be more severe. Although blood transfusions and organ donations have also been observed, the Aedes aegypti mosquito is the primary vector for the transmission of dengue. Infection causes a continuum of clinical illness, from asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Through our literature review, we found two age-stratified dengue seroprevalence surveys conducted in Bangladesh, one in Dhaka city conducted in 2012 [20] and one conducted at the national level in 2022 [19]. These datasets report rather different age-dependent susceptibility profiles, with the national survey (performed 10 years after the one in Dhaka city) reporting a higher FOI estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Through our literature review, we found two age-stratified dengue seroprevalence surveys conducted in Bangladesh, one in Dhaka city conducted in 2012 [20] and one conducted at the national level in 2022 [19]. These datasets report rather different age-dependent susceptibility profiles, with the national survey (performed 10 years after the one in Dhaka city) reporting a higher FOI estimate.…”
Section: Discussionmentioning
confidence: 99%